2011
DOI: 10.4038/jas.v5i2.2782
|View full text |Cite
|
Sign up to set email alerts
|

Impact of conservation tillage under organic mulches on the reproductive efficacy and yield of quality protein maize

Abstract: The present study was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 16 publications
2
9
0
Order By: Relevance
“…In our study, the alternative tillage plus rice residue retention either partially or fully increased the grain yield of maize. Our results agree with [37] who concluded that, compared with full straw removal, 50% straw retention increased grain yield of maize by 32%, and with [41] who also reported higher maize yields under ZT with rice straw retention. Our study also showed significantly higher mungbean yield with full residue retention compared with no retention.…”
Section: Tillage and Residue Management Effect On Crop And System Prosupporting
confidence: 93%
“…In our study, the alternative tillage plus rice residue retention either partially or fully increased the grain yield of maize. Our results agree with [37] who concluded that, compared with full straw removal, 50% straw retention increased grain yield of maize by 32%, and with [41] who also reported higher maize yields under ZT with rice straw retention. Our study also showed significantly higher mungbean yield with full residue retention compared with no retention.…”
Section: Tillage and Residue Management Effect On Crop And System Prosupporting
confidence: 93%
“…The suppression of weed biomass due to the rice straw is probably due to little transmission or no transmission of solar radiation through residue [22]. Similar result was obtained by [23] in quality protein maize (QPM) due to rice straw. [24] reported that atrazine (0.75 kg/ha) as preemergence and then followed by 2, 4-D (1 kg/ha) as postemergence at 30 DAS recorded significant less seed bank of weed over mechanical weeding.…”
Section: Total Dry Weight Of Weedsmentioning
confidence: 67%
“…Similarly, research dose of fertilizer had significantly (p≤0.01) earlier days to silking in comparison with farmer dose of fertilizer respectively (Table 1). Khan and Parvej (2010) reported significantly earlier silking in quality protein maize (QPM) when rice straw was used as mulch and significantly earlier silking as the nitrogen rate increases from 120 and 160 to 200 kg ha -1 (Dawadi and Sah, 2012). Similarly, earlier silking was observed with high dose of phosphorus (Amanullah et al, 2010) and potash (Asif et al, 2007).…”
Section: Resultsmentioning
confidence: 97%
“…But weed management factor did not influence significantly on the physiological maturity of maize (Table 1). Khan and Parvej (2010) reported significantly earlier days to maturity in tilled condition as compared with no tilled condition in QPM. BK et al (2013) reported that the residue retained treatment had significantly longer days to maturity than residue removed treatment.…”
Section: Physiological Maturitymentioning
confidence: 86%
See 1 more Smart Citation